The Role of Expenditure Components in Nepal's Import from India. (March 2014) - Budha, Birendra Bahadur
This article investigates the role of the final expenditure components in determining Nepal's imports from India using the Autoregressive Distributed Lag approach based on the annual data for the period 1975–2011. The results of bounds testing procedure show that there exists the cointegration between Nepal's imports from India and its determinants: personal consumption expenditure, government consumption expenditure, investment, exports and relative prices. Among the expenditure components, personal consumption expenditure is a major determinant of import demand from India, with its significant positive impact. The government expenditure is found to have no significant impact on Nepal's imports from India. Gross domestic investment and exports have negative impact on Nepal's import demand from India, whereas the relative prices have positive impact, indicating lack of substitutes for Indian imports. Trade liberalization also has positive impact on Nepal's import from India.